2022
DOI: 10.3390/foods11182813
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn Juice Simulation System for Pectin and Polyphenol Adsorption Behavior: Kinetic Modeling Properties and Identification of the Interaction Mechanism

Abstract: The interaction between polyphenols and polysaccharides plays an important role in increasing the turbidity stability of fruit juice and improving unpleasant sensory experiences. The binding adsorption behavior between hawthorn pectin (HP) and polyphenols (epicatechin and chlorogenic acid) accorded with the monolayer adsorption behavior driven by chemical action and were better fitted by pseudo-second order dynamic equation and Langmuir model. The HP binding sites (Qm) and adsorption capacity (Qe) to epicatech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Interestingly, compared to the non-pectin fraction, the crude pectin fraction isolated from red okra pod extract showed significantly higher TPC and TFC (Figure 6). Many studies have reported that pectin has a strong binding effect with polyphenols due to its structural characteristics [56][57][58][59][60][61][62]. Pectin is strongly bonded due to high water interaction and hydrogen bonds between tannins [58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, compared to the non-pectin fraction, the crude pectin fraction isolated from red okra pod extract showed significantly higher TPC and TFC (Figure 6). Many studies have reported that pectin has a strong binding effect with polyphenols due to its structural characteristics [56][57][58][59][60][61][62]. Pectin is strongly bonded due to high water interaction and hydrogen bonds between tannins [58].…”
Section: Discussionmentioning
confidence: 99%